Imaging Prevalence of Sigmoid Sinus Dehiscence among Patients with and without Pulsatile Tinnitus. (May 2014) - Schoeff, Stephen; Nicholas, Brian; Mukherjee, Sugoto; Kesser, Bradley W.
Objective: Define the radiographic prevalence of sigmoid sinus diverticulum or dehiscence (SSDD) in patients with and without pulsatile tinnitus (PT). Study Design: Case series with chart review. Setting: Tertiary care university medical center. Subjects: Patients imaged between January 1, 2003, and December 31, 2012. Methods: Two groups were evaluated for SSDD. The first ("PT") included patients whose radiology report indicated a clinical history of PT (n = 37 symptomatic ears in 30 patients). The second ("non-PT") included all patients undergoing temporal bone high resolution CT (HRCT) between November 2011 and November 2012 (n = 308 ears in 164 patients) for reasons other than pulsatile tinnitus. Primary outcome measure was the radiographic presence of SSDD. Covariates including age, gender, body mass index (BMI), and audiometric data were analyzed by independent t tests and Fisher's exact test. Results: Within the PT group, SSDD was identified in 24% of ears (9/37) and 23% of patients (7/30); all SSDD patients were female ( P = .024). Patients with SSDD were significantly younger ( P = .037). SSDD more frequently caused objective tinnitus ( P = .016). There was no difference in average BMI between those with and those without SSDD. In the non-PT group, SSDD was identified in 2 (both female) of 164 patients (1.2%; 0.6% of ears). The difference in SSDD prevalence between groups was significant ( P < .0001). Conclusions: The prevalence of SSDD in patients with PT was 23%. Among patients with PT, those with SSDD were younger, exclusively female, and presented with objective tinnitus. The prevalence of SSDD among asymptomatic patients in 1 year was 1.2%.